VISUALISASI INTRUSIVE THOUGHTS DALAM KARYA FILM EKSPERIMENTA - Shafy Putra, Muhammad; Wiwid Sintowoko, Dyah Ayu; Permana Zen, Adrian (Telkom University, 2024)
The making of this experimental 昀椀lm en琀椀tled Intrusive Thoughts is a 昀椀lm work that discusses intrusive thoughts, namely nega琀椀ve thoughts in the form of imagina琀椀on or thoughts that are brutal, or appear in the form of violence, sexual, and create cogni琀椀ve disorders that if followed will endanger others. This work is inspired by the phenomenon of intrusive thoughts in the journal